Difficulties Experienced By Students In Learning From Mathematics During The Covid-19 Pandemic - Egitia Fitria (Aksioma Education Journal, 2024)
This study aims to identify the obstacles faced by students learning from during the Covid-19 pandemic. The method used was descriptive qualitative approach, conducted at SMA 5 Palembang City involving 26 students as participants. This study used a questionnaire as a data collection tool, which was distributed to students online via WhatsApp using Google Form. The results showed that the main obstacles faced by students were related to the availability of facilities and inadequate internet connection. Some students do not have adequate access to support online learning, coupled with poor internet network quality, hindering their participation in online learning that requires a stable internet connection. In addition, in dealing with online learning, more creativity is needed from the teacher to prevent boredom and lack of motivation in students. Another obstacle is the limited communication between students and teachers. Which results in difficulties in understanding the learning materials.